HEAT! : A Bank Health Assessment Tool - Ong, Li (IMF Working Papers; Working Paper ;, 2013)
Developments during the global financial crisis have highlighted the importance of differentiating across financial systems and institutions. Assessments of financial stability have increasingly considered the characteristics of individual banks within a financial system, as well as those with significant international reach, to identify vulnerabilities and inform policy decisions. This paper proposes a simple measure of bank soundness, the Bank Health Index (BHI), to facilitate preliminary analyses of individual financial institutions relative to their peers. The evidence suggests that the BHI is useful for a first-pass identification of bank soundness conditions. Automated spreadsheet templates of the bank Health Assessment Tool (HEAT!) are provided for users with access to the BankScope, Bloomberg and/or SNL database(s).